Relationship between Social Behaviour and Academic Performance of Students at Secondary Level in Khyber Pakhtunkhwa: Mir Alam Said, Muhammad Idri , Sajjad Hussain (PJDOL, 2023)
The study explored views of teachers about relationship between social behaviour and academic performance. The objectives of the study were to examine the effects of social behaviour on academic performance; compare academic results of students with social behaviour; investigate the importance of social behaviour on academic performance; and, suggest what necessary steps should be taken to improve the academic performance and social behaviour.